Correlates of cardiorespiratory fitness in a population-based sample of middle-aged adults: cross-sectional analyses in the SCAPIS study - Daniel Arvidsson; Mats Borjesson; Örjan Ekblom; Göran Bergström; Elin Ekblom-Bak; Emerald G Heiland; Daniel Väisänen (BMJ Open, 2022)
Objectives This study aimed to identify main sex-specific correlates of cardiorespiratory fitness (CRF) in a population-based, urban sample of Swedish adults.Design Cross-sectional.Setting Multi-site study at university hospitals, data from the Gothenburg site.Participants A total of 5308 participants (51% women, aged 50–64 years) with a valid estimated VO2max, from submaximal cycle test, in the Swedish CArdioPulmonary bioImage Study (SCAPIS), were included.Primary and secondary outcomes A wide range of correlates were examined including (a) sociodemographic and lifestyle behaviours, (b) perceived health, anthropometrics and chronic conditions and (c) self-reported as well as accelerometer-derived physical activity and sedentary behaviours. Both continuous levels of estimated VO2max as well as odds ratios (OR) and confidence intervals (CI)s of low VO2max (lowest sex-specific tertile) were reported.Results In multivariable regression analyses, higher age, being born abroad, short education, high waist circumference, poor perceived health, high accelerometer-derived time in sedentary and low in vigorous physical activity, as well as being passive commuter, correlated independently and significantly with low VO2max in both men and women (OR range 1.31–9.58). Additionally in men, financial strain and being an ex-smoker are associated with higher odds for low VO2max (OR 2.15; 95% CI 1.33 to 3.48 and OR 1.40; 95% CI 1.09 to 1.80), while constant stress with lower odds (OR 0.61; 95% CI 0.43 to 0.85). Additionally in women, being a regular smoker is associated with lower odds for low VO2max (OR 0.64; 95% CI 0.45 to 0.92).Conclusions The present study provides important reference material on CRF and correlates of CRF in a general middle-aged population, which can be valuable for future research, clinical practice and public health work. If relations are causal, increased knowledge about specific subgroups will aid in the development of appropriate, targeted interventions.